Endosomal trafficking inhibitor EGA can control TLR7-mediated IFNα expression by human plasmacytoid dendritic cells - Wiest, Matthew J.; Baert, Laurie; Gu, Chao; Gayler, Kevin M.; Ham, Hyoungjun; Gorvel, Laurent; Keddis, Mira T.; Griffing, Leroy W.; Joo, HyeMee; Gorvel, Jean-Pierre; Billadeau, Daniel D.; Kane, Robert R.; et al. (Frontiers in Immunology, 2023)
Plasmacytoid dendritic cells (pDC) are the major producer of type 1 IFN in response to TLR7 agonists. Aberrant TLR7 activation and type 1 IFN expression by pDCs are linked to the pathogenesis of certain types of autoimmune diseases, including systemic lupus erythematosus (SLE). This study investigated the underlying mechanisms for TLR7-mediated cytokine expression by pDCs using a late endosome trafficking inhibitor, EGA (4-bromobenzaldehyde N-(2,6dimethylphenyl) semicarbazone). We found that EGA treatment decreased IFNα expression by pDCs stimulated with imiquimod (R837), single-stranded RNA40, and influenza virus. EGA also decreased TNFα expression and secretion by R837-stimulated pDCs. Mechanistically, EGA treatment decreased phosphorylation of IKKα/β, STAT1, and p38, and prolonged degradation of IκBα. Furthermore, EGA treatment decreased the colocalization of 3F, a substituted adenine TLR7 agonist, with LAMP1 + compartments in pDCs. EGA was also capable of diminishing IFNα expression by SLE pDCs treated with R837 or live PR8/A/34 influenza viruses. Therefore, we concluded that trafficking of TLR7 agonists to LAMP1 + compartments is important for IFNα expression by pDCs. Data from this study support additional examinations of the potential benefits of EGA in treating type 1 IFN-associated inflammatory diseases in the future.